2007
DOI: 10.2109/jcersj.115.434
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Pyrolysis of Crocidolite and Amosite using Calcium Salts as a Flux

Abstract: Two kinds of materials, sprayed-on crocidolite and sprayed-on amosite, containing crocidolite and amosite respectively, were treated with aqueous acetic acid solution, the pH of which was adjusted with an ammonium acetate buffer at 5, in order to remove soluble components of cement. The liquids were filtrated with a membrane filter, and the residue collected as crocidolite samples and amosite samples, respectively. The Crocidolite and amosite thus obtained were heated up to 600-1300? C for 1h. Then, power X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…3. In the region 3,000-4,000 cm 3,681-3,686 cm -1 can be assigned to the surface Mg-OH stretch vibration, whereas the second band can be linked to the inner Mg-OH stretch vibration [38]. This confirms the assignment of the OH doublet to the external and internal Mg-OH groups in chrysotile asbestos [33].…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…3. In the region 3,000-4,000 cm 3,681-3,686 cm -1 can be assigned to the surface Mg-OH stretch vibration, whereas the second band can be linked to the inner Mg-OH stretch vibration [38]. This confirms the assignment of the OH doublet to the external and internal Mg-OH groups in chrysotile asbestos [33].…”
Section: Resultssupporting
confidence: 74%
“…11). It may be caused by the loss of chemical bonded water [37] or in accordance with Fujishige et al [38] by partially melted fibers. The second way was confirmed by TG analysis (Fig.…”
Section: Amphibole Asbestosmentioning
confidence: 55%
See 2 more Smart Citations
“…Recent papers revealed that the addition of calcium salts was effective to decrease the decomposition temperatures of asbestos [17,18]. At low temperatures, the calcium salts gave a melt which acted as a flux.…”
Section: Introductionmentioning
confidence: 99%